1989
DOI: 10.1128/jb.171.12.6555-6565.1989
|View full text |Cite
|
Sign up to set email alerts
|

envM genes of Salmonella typhimurium and Escherichia coli

Abstract: Conjugation and bacteriophage P1 transduction experiments in Escherichia coli showed that resistance to the antibacterial compound diazaborine is caused by an allelic form of the envM gene. The envM gene from Salmonella typhimurium was cloned and sequenced. It codes for a 27,765-dalton protein. The plasmids carrying this DNA complemented a conditionally lethal envM mutant of E. coli. Recombinant plasmids containing gene envM from a diazaborine-resistant S. typhimurium strain conferred the drug resistance pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 21 publications
(11 reference statements)
1
79
0
Order By: Relevance
“…E. coli SFIOO (ompn was described previously [ I l l . E. coli J P l l l 1 , which carries the temperaturesensitivefubl allele [7], was first described by Egan and Russell 1121. E. coli FTlOO and FTlOl are an isogenic pair of strains derived from E. coli JP1 11 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…E. coli SFIOO (ompn was described previously [ I l l . E. coli J P l l l 1 , which carries the temperaturesensitivefubl allele [7], was first described by Egan and Russell 1121. E. coli FTlOO and FTlOl are an isogenic pair of strains derived from E. coli JP1 11 1.…”
Section: Methodsmentioning
confidence: 99%
“…Incubation of E. coli with diazaborine leads to pleiotropic effects on lipid biosynthesis 171. A point mutation in thefib1 gene, which results in a Gly93+Ser exchange in the polypeptide chain, is responsible for the diazaborine-resistant phenotype in E. coli and Salmonella typhimurium [7,81. Another mutation in the fuhl gene leading to a Ser24l+Phe exchange in the FabI protein causes temperature-sensitive growth in E. coli [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over-expression of prolipoprotein signal peptidase (gene product of lsp) was shown to confer its host cells a high level of resistance to globomycin, an inhibitor of lipoprotein signal peptidase [38]. Turnowsky and colleagues [39] demonstrated that overexpression of EnvM (FabI) protein from the plasmid-borne gene conferred resistance to diazaborine, a specific inhibitor for FabI. Tsay and coworkers [40] screened a thiolactomycin sensitive E. coli strain against an E. coli genomic library for recombinant plasmids that conferred resistance to thiolactomycin, an inhibitor for FabB protein (β-ketoacyl-acyl carrier protein synthase I).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tuberculosis agent, isoniazid targets the FabI homologue (InhA) of Mycobacterium tuberculosis [6]. Diazaborines were also found to inhibit FabI [7]. Although an alternative enoyl-ACP reductase, FabK, which displays no significant sequence homology to FabI, was identified in Streptococcus pneumoniae, Enterococcus faecalis and Pseudomonas aeruginosa [8], genomic studies have revealed that most bacteria possess FabI as the sole enoyl-ACP reductase.…”
Section: Introductionmentioning
confidence: 99%